2004
DOI: 10.1253/circj.68.898
|View full text |Cite
|
Sign up to set email alerts
|

In Normoglycemic Koreans, Insulin Resistance and Adipocity are Independently Correlated With High Blood Pressure

Abstract: yperinsulinemia is known to be associated with various cardiovascular risk factors, including high triglyceride concentrations, low high-density lipoprotein (HDL) cholesterol concentrations, high blood pressure (BP), and obesity. 1-3 However, there is some controversy about the role of insulin resistance (IR) in the regulation of BP. Several prospective studies have linked insulin concentrations to the incidence of hypertension [4][5][6] and it has been suggested that hyperinsulinemia and/or IR plays a role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Increased insulin sensitivity has also been found in hypertensive patients with normal mean BMI [20]. Conversely, others have found cross-sectionally that elevated BMI, waist circumference and insulin resistance are associated with high BP [21], and that the insulin resistance is directly correlated to the severity of hypertension [22]. It has also been suggested that a lower BMI might be associated with a decreased sodium retention by the kidney, related to serum insulin levels or other factors [20].…”
Section: Discussionmentioning
confidence: 99%
“…Increased insulin sensitivity has also been found in hypertensive patients with normal mean BMI [20]. Conversely, others have found cross-sectionally that elevated BMI, waist circumference and insulin resistance are associated with high BP [21], and that the insulin resistance is directly correlated to the severity of hypertension [22]. It has also been suggested that a lower BMI might be associated with a decreased sodium retention by the kidney, related to serum insulin levels or other factors [20].…”
Section: Discussionmentioning
confidence: 99%
“…First, insulin resistance and insulin concentration are also associated with blood pressure ( 19 ). Insulin and leptin are reported to cooperate in the modulation of vascular tone ( 20 -22 ), and insulin has been shown to stimulate leptin production ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study population was originally recruited during a health survey on the prevalence of thyroid disease and diabetes mellitus in the district of Baoshan in Shanghai, China. Since existing research conducted in other populations have suggested that insulin resistance may also be associated with blood pressure, (7,8) we investigated the relationships among serum TSH level, insulin resistance and blood pressure. …”
mentioning
confidence: 99%